2015
DOI: 10.1016/j.jneuroim.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of thymoquinone in activated BV-2 microglial cells

Abstract: Thymoquinone (TQ), the main pharmacological active ingredient within the black cumin seed (Nigella sativa) is believed to be responsible for therapeutic effects on chronic inflammatory conditions such as arthritis, asthma and neurodegeneration. In this study, we evaluated the potential anti-inflammatory role of TQ in lipopolysaccharide (LPS)-stimulated BV-2 murine microglia cells. The results obtained indicated that TQ was effective in reducing NO2- with an IC50 of 5.04 μM, relative to selective iNOS inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…Previously our lab has demonstrated the anti-inflammatory properties of TQ in BV-2 microglia solely activated with LPS (Taka et al, 2015). However, in this study we co-activated the BV-2 microglial cells with LPS and INFγ because the two pro-inflammatory agents work synergistically to induce maximal transcriptional responses, enhancing the release of NO in microglia upon activation (Paludan, 2000, Pawate et al, 2004, Yoo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously our lab has demonstrated the anti-inflammatory properties of TQ in BV-2 microglia solely activated with LPS (Taka et al, 2015). However, in this study we co-activated the BV-2 microglial cells with LPS and INFγ because the two pro-inflammatory agents work synergistically to induce maximal transcriptional responses, enhancing the release of NO in microglia upon activation (Paludan, 2000, Pawate et al, 2004, Yoo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TQ is a ROS scavenger (Mansour et al, 2002; Badary et al, 2003) capable of reducing the levels of several ROS and lipid/protein oxidation markers in liver and kidney tissue, microglia and macrophages (El-Mahmoudy et al, 2002; Attia et al, 2010; Mahmoud et al, 2014; Cobourne-Duval et al, 2016). Likewise, the anti-inflammatory properties of TQ treatment have been demonstrated in mast cells, microglia, kidney, and liver (El Gazzar et al, 2007; Al-Malki and Sayed, 2014; Mahmoud et al, 2014; Taka et al, 2015). Furthermore, studies have also indicated that TQ treatment provides neuroprotection against amyloid β-induced and α-synuclein-induced neurotoxicity (Khan et al, 2012, Alhebshi et al, 2013, Alhebshi et al, 2014), traumatic brain injury (Gülşen et al, 2016), environmental neurotoxins (Kanter, 2008; Radad et al, 2009; Radad et al, 2014), and transient forebrain ischemia (Al-Majed et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TQ is a principal active ingredient of the Nigella sativa seeds (5). It has been informed to exhibit various pharmacological activities, such as antihypertensive (6), anti-inflammatory and anti-cancer (7,8), antidiabetic (9) and analgesic properties (10). TQ is also reported to possess strong antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a previously conducted optimization study in our lab, 1 μg/mL of LPS was found to be the optimum concentration for BV-2 microglial cells activation. (Taka et al, 2015). Others also indicated similar LPS dose (Pinho et al, 2011).…”
Section: Experimental Sectionsmentioning
confidence: 99%